Reviewed Study on Ministries and Political Parties during the Period of Study 1947-1969: The Impact of Agricultural Policy and Administrative Measures on Economic Development in Madras State (1947-1969) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
After the Independence the legislature did brilliant managerial measures without anticipating anything consequently from people in general. The government official completely engaged with the improvement procedure. The administration accomplished the work in an arranged way. The cancelation of zamindari framework, nationalization of transport, advancement of nearby self-government, forbiddance and instructive measures assisted with building a solid establishment for future improvement of Madras state. Agricultural assumed a critical job in financial turn of events. Tamilnadu sent out for the most part agrarian items like Jute, cotton, materials, tea, oil seeds, flavors, tobacco, wood, lumber and millets. Farming pay went up dependent on the interest of fabricated products like material and Sugar.